Konsepsi Perlindungan Hukum Terhadap Anak Yang Menjadi Pelaku Dan Korban Kekerasan Seksual Dalam Sistem Peradilan Pidana Anak - Abdul Kadir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2023)
The high rate of sexual violence experienced by children in Indonesia is increasing which has become a special concern for both the Central and Regional Governments and the participation of the community. This study aims to analyze the conception of legal protection for children in the Draft Criminal Code (RKUHP) regarding the criminal responsibility of children in the Child Criminal Justice System (SPPA) in Indonesia, where the perpetrators and victims are children. 1. What is the concept of the legal regulation of the RKUHP as a form of protection for children whose perpetrators and victims of sexual violence are children. 2. What are the legal remedies for perpetrators and victims of sexual violence in juvenile criminal justice. The results of the study can be concluded that, the RKUHP is a comprehensive criminal law reform by following the conditions and developments that live in society, imprisonment as far as possible is not imposed if it is found that the defendant is a child and children under the age of 14 (fourteen) years cannot be sentenced. criminal acts and can only be subject to action, on the one hand, the perpetrator remains accountable to the victim. SPPA prioritizes settlement with a restorative justice approach based on the Decree of the Director General of the General Court of Justice Number 1691/DJU/SK/P.00/12/2020 concerning Guidelines for the Implementation of Restorative Justice in the General Courts. In addition, Diversion can also be applied, which is the transfer of the settlement of children's cases from the criminal justice process to processes outside of criminal justice. In the event that Diversion is unsuccessful or does not meet the requirements, the judge seeks a decision with a restorative justice approach as regulated by Law Number 11 of 2012 concerning SPPA, the judge proactively encourages related parties to seek peace while still prioritizing the principle of the best interests of the child and the sentencing process is the last resort while not ignoring the rights of the child.